Եկեղեցւոյ ազատականացման միտումներ արեւմտահայ աւետարանական շրջանակներու մէջ - Յարութիւն Սելիմեան (ՀՀ ԳԱԱ հրատ.)
В первой половиние XIX в. духовно-культурная переориентация шла в сторону национального самосознания армянского народа, и это ярко проявилось в патриотических настроениях духовного творчества авторов романтиков того периода (М. Налбандян, Р. Патканян, С. Шаазиз). The creed inclination of the protestant publications, “Shtemaran pitani giteleats”/Zmurnia, 1839-1854, "Avetaber"/ Constantinople, 1855-191", “Awyetaber mankants”/ Constantinople, 1908-1915, and in other periodicals was towards the education and upbringing of the Armenian people and the development of the Armenian language.
Keywords: Christianity; Journalism; The periodical Press, etc.; History of the Armenian Church